Hemoperitoneum secondary to intercostal arterial bleeding in a trauma patient. Issue 1 (20th January 2017) - Laeeq, K.; Cheung, S.; Phillips, B.
Abstract: Blunt trauma resulting in rib fractures can be associated with hemothorax, pneumothorax, pulmonary contusions or less frequently chest and abdominal wall hematomas. Our case describes the first report of hemoperitoneum secondary to intercostal arterial bleeding from blunt trauma in a patient on anticoagulation.